2021
DOI: 10.1038/s41398-021-01439-y
|View full text |Cite
|
Sign up to set email alerts
|

OPRD1 SNPs associated with opioid addiction are cis-eQTLs for the phosphatase and actin regulator 4 gene, PHACTR4, a mediator of cytoskeletal dynamics

Abstract: Several OPRD1 intronic variants were associated with opioid addiction (OD) in a population-specific manner. This follow-up study aims to further characterize the OPRD1 haplotype pattern of the risk variants in different populations and apply in silico analysis to identify potential causal variants. A population-specific haplotype pattern was revealed based on six OPRD1 eQTL SNPs and five common haplotypes were identified in a sample of European ancestry (CEU). A European-specific haplotype (‘Hap 3’) that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some genes are worth noting. For instance, OPRD1, which was identi ed by positional mapping, is a member of opioid receptor signaling pathway and was nominated as SUD-related in some small studies [39][40][41] , but was not reported as SUD-related in the GWAS catalog 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Some genes are worth noting. For instance, OPRD1, which was identi ed by positional mapping, is a member of opioid receptor signaling pathway and was nominated as SUD-related in some small studies [39][40][41] , but was not reported as SUD-related in the GWAS catalog 36 .…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study, Agrawal et al (2020) report that subjective responses to initial opioid exposure differ between people who progress to developing opioid use disorder and those who do not. This inter-individual variability in opioid responses and addiction liability has a significant genetic component (Glatt et al, 2007;Goldman et al, 2005;Levran et al, 2021;Reed & Kreek, 2021). Indeed, several genes have been associated with altered opioid response, including those that encode for opioid receptors, metabolizing enzymes, drug transporters, and proteins involved in other modulating systems such as descending adrenergic and serotonergic inputs (Klepstad et al, 2005;Nielsen et al, 2015;Stamer et al, 2005).…”
mentioning
confidence: 99%